Advances in N‐Heterocyclic Carbene Catalysis for Natural Product Synthesis. Issue 37 (23rd July 2020) - Que, Yonglei; He, Haibing
Abstract : N‐heterocyclic carbenes (NHCs) efficiently catalyze new bond formations with high regio‐ and stereoselectivity through umpolung and non‐umpolung processes. These processes typically involve four species: Breslow intermediates, homoenolates, enolates, and α, β‐unsaturated acyl azoliums. Organic syntheses are increasingly relying on NHC catalysis, and this minireview highlights developments in NHC‐catalyzed reactions that, over the past two decades, have been used as key steps in the total syntheses of natural products. Crucial intermediates and reaction mechanisms are presented in detail. Abstract : This Minireview gives an overview of the four important intermediates generated in N‐heterocyclic carbene catalysis that have been applied in the total synthesis of natural products: Breslow intermediates, homoenolates, enolates, and α, β‐unsaturated acyl azoliums.